2020
DOI: 10.1177/1533033820959355
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Targeted Microbubble Destruction-Mediated miR-206 Overexpression Promotes Apoptosis and Inhibits Metastasis of Hepatocellular Carcinoma Cells Via Targeting PPIB

Abstract: Background: Ultrasound-targeted microbubble destruction (UTMD) has been found to be an effective method for delivering microRNAs (miRNAs, miRs). The current study is aimed at discovering the potential anti-cancer effects of UTMD-mediated miR-206 on HCC. Methods: In our study, the expressions of miR-206 and peptidyl-prolyl cis-trans isomerase B (PPIB) in HCC tissues and cells were detected by quantitative real-time polymerase chain reaction (qRT-PCR). PPIB expressions in HCC and adjacent normal tissues were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additively, research revealed that UTMD-mediated miR-767 inhibition resulted in a more significant suppressive effect on NSCLC tumour proliferation, migration and invasion [ 10 ]. Moreover, in other cancers or malignancies, such as hepatocellular carcinoma [ 11 ], synergistic therapeutic effects of UTMD were also widely recognized. Consequently, UTMD has been considered a promising adjunct to targeted therapy for human malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Additively, research revealed that UTMD-mediated miR-767 inhibition resulted in a more significant suppressive effect on NSCLC tumour proliferation, migration and invasion [ 10 ]. Moreover, in other cancers or malignancies, such as hepatocellular carcinoma [ 11 ], synergistic therapeutic effects of UTMD were also widely recognized. Consequently, UTMD has been considered a promising adjunct to targeted therapy for human malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, miR206 was not differentially expressed in the TvN comparison; however, it was significantly upregulated in the F1vT comparison with a fold change of 26.01. Wu et al showed that the expression of miR-206 inhibited hepatocellular carcinoma cell migration and invasion while promoting apoptosis by targeting Peptidylprolyl Isomerase B (PPIB) [ 58 ]. Another study evaluated the expression of 41 genes as a function of in vitro radioresistance in the NCI-60 cancer cell line panel and found that PPIB had the strongest direct correlation.…”
Section: Discussionmentioning
confidence: 99%
“…PPIB is associated with malignant progression, and gene regulation has been noted by some researchers [ 16 ]. Overexpression of miR-206 promotes apoptosis and inhibits the metastasis of HCC cells by targeting PPIB [ 17 ]. UGT2B15 is a functional member of the UGT2B subfamily.…”
Section: Discussionmentioning
confidence: 99%